Programa de evaluación "PEPAFA" para mejorar el nivel de aprendizaje del Área Ciencia y Ambiente en los estudiantes de 3° grado de la Institución Educativa Nº 00623, Azunguillo del distrito de Elías Soplín Vargas, Rioja. - Naval Naval, Elizabeth (2007)
The present investigation has had as general objective, to elaborate and to apply the evaluation program "PEPAFA" to improve the level of learning of the area Science and Atmosphere in the students of the 3° grade of the lnstitution Educational nº 00623, Azunguillo of Elías's district Soplín Vargas, in the year 2007. I study that is justified for their relevance in the educational field~ specifically in the teaching process and learning of the area Science and Atmosphere that it is developed in the level of primary education of the basic education to regulate and to have allowed to elevate the level of the students' learning in the aforementioned curricular area. The theoretical conception that sustains the present study is based on the theoretical positions of Rosebushes (1990), Carreña (1994), Fuentes (1998), Zayas (2005) and Matías and other (2005) who they consider to the education like a complex process in all its dimensions and more even if we refer to its evaluation process considering 1 don't eat it a stage of the teaching process and learning but like part of the same process with the only purpose of improving it. Supported in these positions the hypotheses they were formulated: Alternative hypothesis: lf it is elaborated and it applies the evaluation program "PEPAFA", then he/she improved the level of learning of the area Science and Atmosphere significantly in the students of the 3° grade the lnstitution Educational nº 00623, Azunguillo of Elías's district Soplín Vargas, Rioja - 2007; Null hypothesis: lf it is elaborated and it applies the evaluation program "PEPAFA", then he/she won't improve the level of learning of the area Science and Atmosphere significantly in the students of the 3° grade of the Institution Educational nº 00623, Azunguillo of Elías's district Soplín Vargas, Rioja - 2007. The sample was conformed by 25 students, 25 parents and 01 professor of the 3° of the I.E. Nº 00623. Azunguillo; that is to say the experimental group and of name quantity for the group control. To the sample he/she was applied the evaluation program "PEPAFA" during one month at the end of which you applies the search test to determine the influence of the same one. After the analysis and respective interpretation, the significant influence of the program was demonstrated in the level of the students' of the 3° of the l. learning E. Nº 00623. Azunguillo.